Empire of Improvisation : Taxation and Governance in Colonial Indonesia - Manse, Maarten (Asian Studies E-Books Online, Collection 2026., 2026)
Throughout colonial Indonesia, a common method to determine a boy's taxable age was to loop a rope around the chest. If the boy's head fitted through, his chest was still too small and he was too young; if not, he owed the government tax. Analysing unique archival sources from across Indonesia, this book shows how such pragmatic, locally embedded methods often overshadowed formal tax procedures, which colonial officials advanced as civilizing instruments of modernisation and state-power. It exposes taxation as a process in which improvisation, indigenous customs and everyday negotiations tied together formal regulations and ordinary local realities. A must-read for historians of empire in and beyond Southeast Asia, the book reshapes our understanding of colonial governance, challenging grand theories of colonial state formation by revealing the practicalities of everyday colonial rule and the agency of local actors manipulating the system from within.